(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
The territory of any state and nation is the backbone of its independence. When the people’s interest to improve their livelihood level by putting land into economic circulation, an appropriate use of land resources is becoming the crucial issue that to be resolved foremost. In today’s globalized socio-economic system it is very important for further development of Mongolia, not destroying the traditional nomadic livestock husbandry practices, to develop and implement a concept of pasture management adapted to these practices based on the territory and communities that would be economically efficient, environment friendly and supportive to social progress. Therefore, developing a policy on pastureland use in accordance with this concept and implementing the future policy on development of the country as a whole, aimags and rural areas through planning of pastureland and taking efficient and complex measures for pastureland issues tend to be one of the urgent problems. In this connection, there is a need to determine policy on and take measures for appropriate pasture management to make efficient pasture use plan adapted to ecosystem management. The research on these hersder’s usage of pasture land, management of pasture land, cooperative organization, pastoral legislative, cattle breeding and service of cattle breeding and its results as well as economy and social status of herders within the research has held in 5 provinces such as Arkhangai, Bulgan, Gobi-Altai, Khuvsgul and Khentii, 15 sub-provinces are included. As a result of this research pasture land is getting worse due to arbitrary and unplanned usage of pasture land, to move nearer to the rivers, over usage of grazing capacity because of human faulty activities. Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 51-54